Productivity change in the efficiency of the insurance and Takaful industry of Pakistan - Taib, Che Azlan; Ashraf, Muhammad Saleem; Ahmad Razimi, Mohd Shahril (Allied Business Academies, 2018)
This paper will use the Malmquist Productivity Index (MPI) synchronized with the inputoriented Data Envelopment Approach to evaluating the productivity change for the insurance and takaful industry of Pakistan for the period of 2008 to 2016. Total factor productivity (TFP) change for the industry is measured and then it is decomposed into Technical efficiency change and technological change to measure the reason for the productivity change. The results of the study reveal that overall insurance industry in Pakistan was enjoying the increase in the total factor productivity during the above mentioned period. Change in factor productivity for the takaful companies was better than insurance firms. Therefore, pure technical efficiency and scale efficiency made takaful operators more productive comparative to the conventional insurers.